CSF Free Light Chains as a Marker of Intrathecal Immunoglobulin Synthesis in Multiple Sclerosis: A Blood-CSF Barrier Related Evaluation in a Large Cohort - Senel, Makbule; Mojib-Yezdani, Fatemeh; Braisch, Ulrike; Bachhuber, Franziska; Lewerenz, Jan; Ludolph, Albert C.; Otto, Markus; Tumani, Hayrettin (Frontiers in Immunology, 2019)
Objectives: The importance of immunoglobulin G (IgG) oligoclonal bands (OCB) in the diagnosis of multiple sclerosis (MS) was reaffirmed again in the recently revised MS diagnostic criteria. Since OCB testing is based on non-quantitative techniques and demands considerable methodological experience, measurement of CSF immunoglobulin free light chains (FLC) has been suggested as quantitative alternative to OCB. We aimed to establish reference values for FLC measures and evaluate their diagnostic accuracy with regard to the diagnosis of MS. Methods: Immunoglobulin kappa (KFLC) and lambda (LFLC) free light chains were prospectively measured by nephelometry in CSF and serum sample pairs in 1224 patients. The analysed cohort included patients with MS, other autoimmune or infectious inflammatory diseases of the nervous system as well as 989 patients without signs for nervous system inflammation. Results: Regarding diagnosis of MS, the diagnostic sensitivity and specificity of intrathecal KFLC ratio were 93.3% and 93.7% using the CSF-serum albumin ratio-dependent reference values, 92.0% and 95.9% for intrathecal KFLC ratio applying the ROC-curve determined cut-off levels, 62.7% and 98.3% for IgG index, 64.0% and 98.8% for intrathecal IgG synthesis according to Reiber diagrams, and 94.7% and 93.3% for OCB. Diagnostic sensitivity and specificity of intrathecal LFLC were clearly lower than KFLC. Conclusions: Intrathecal KFLC and OCB showed the highest diagnostic sensitivities for MS. However, specificity was slightly lower compared to other quantitative IgG parameters. Consequently, CSF FLC may not replace OCB, but it may support diagnosis in MS as a quantitative parameter.